Analisis Koreksi Fisikal Atas Laporan Keuangan Komersial Dalam Menentukan Pajak Penghasilan (PPH) Badan PT XXX - Safrina Hasanah; Erna Sulistyowati (JURNAL ILMIAH NUSANTARA, 2024)
Commercial financial reports are records containing financial information held by a company in a certain period which are prepared based on the provisions of applicable Financial Accounting Standards, while fiscal reports are financial reports prepared using methods, standards or accounting practices that are in accordance with tax regulations. The purpose of this research is to find out whether all income or expenses that have been corrected in the fiscal correction process are in accordance with applicable tax regulations, as well as to find out the amount of tax income that PT. XXX based on the fiscal corrections made. This research uses a descriptive method that focuses on the financial reports of PT. XXX 2023. The results of this research show that fiscal corrections were made to the income account resulting from negative fiscal corrections amounting to IDR 6,268,018 and the corporate income tax to be paid by PT XXX amounting to IDR 26,972,550